Adhesive sheets and electronic devices

By using the adhesive sheet of a foamed substrate with a specific configuration, the problem of difficulty in peeling off the organic EL information display device and insufficient follow-up to the high-segment difference part is solved during disassembly of the electronic device, which achieves good peeling performance and follow-up, and avoids the problem of water immersion.

CN110662812BActive Publication Date: 2025-03-21DIC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201880034093.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-06-14
Filing Date
2018-05-29
Publication Date
2025-03-21
Estimated Expiration
2038-05-29

AI Technical Summary

Technical Problem

The conventional adhesive sheet is difficult to peel off the organic EL information display device when disassembly of the electronic device, and the following of the high-segment difference area is insufficient, which can easily cause water immersion.

Method used

A foamed substrate containing 30 to 90% by mass of ethylene vinyl acetate copolymer (EVA) and/or ethylene acrylic acid copolymer (EAA) is used, and an adhesive sheet with an apparent density of 0.20 g/cm3 to 0.60 g/cm3 and a tensile elastic modulus of 10 MPa to 35 MPa is used to ensure that it can be peeled off without destroying the organic EL information display device during disassembly of the electronic device and has good following.

Benefits of technology

It achieves good peeling performance and good follow-up to high-segment differences in electronic equipment when disassembling, avoids the problem of water immersion, and ensures bonding strength and waterproofness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002284669260000181
    Figure BDA0002284669260000181
  • Figure BDA0002284669260000191
    Figure BDA0002284669260000191
  • Figure BDA0002284669260000192
    Figure BDA0002284669260000192
Patent Text Reader

Abstract

The problem to be solved by the present invention is to provide an adhesive sheet having re-peelability that allows an organic EL information display device to be easily peeled off when disassembling an electronic device, and having good followability to the high step portion of the adherend. The present invention relates to an adhesive sheet having an adhesive layer directly on one or both sides of a foam substrate or having an adhesive layer separated by other layers, wherein the foam substrate contains 30 to 90% by weight of ethylene vinyl acetate copolymer (EVA) and / or ethylene acrylic acid copolymer (EAA), and the apparent density of the foam substrate is 0.20 g / cm 3 ~0.60g / cm 3 And the tensile elastic modulus in the flow direction is 10MPa to 35MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet that can be used in the production of various articles, such as electronic devices such as car navigation systems, personal computers, televisions, and smartphones. Background Art

[0002] Adhesive sheets using a foam as a base material are widely used, for example, to fix two or more housings, rechargeable batteries, circuit boards, and the like constituting electronic devices.

[0003] As the aforementioned adhesive sheet, for example, an adhesive sheet with a foam sheet as a substrate is known, the foam sheet being characterized in that it is a resin foam formed by foaming a resin composition, the resin composition containing a polyolefin resin and an incompatible resin relative to the polyolefin resin in a ratio of 90:10 to 60:40, and the average major diameter of the island portion of the sea island structure formed by the aforementioned polyolefin resin and the incompatible resin is greater than 1 μm (for example, refer to patent document 1).

[0004] In addition, electronic devices such as televisions and smartphones are being waterproofed. Therefore, adhesive sheets used to fix components are required to have the ability to follow the step of housings, circuit boards, etc. and have high bonding strength to prevent water ingress. In recent years, from the perspective of design, curved surfaces and complex-shaped panels have been used more frequently, and adhesive sheets are expected to have the ability to follow uneven surfaces and high step differences.

[0005] Furthermore, in recent years, in order to realize high-definition information display, the use of organic EL information display devices has been increasing. Since such organic EL display devices are expensive, they are required to be reused when repairing electronic equipment. In conjunction with this, adhesive sheets for fixing information display devices are required to have re-peelability, that is, to be able to be easily peeled off without damaging the organic EL information display device during disassembly during repair.

[0006] As a means to solve such problems, reinforcing the strength of the foam substrate of the adhesive sheet is generally effective. However, adhesive sheets using high-strength foams are not sufficiently conformable to the step portion of the adherend and are prone to water infiltration from the outside.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-274073 Summary of the invention

[0010] Problems to be solved by the invention

[0011] An object of the present invention is to provide an adhesive sheet having removable performance that allows an organic EL information display device or the like to be easily removed when disassembling an electronic device, and having good followability to a high-step portion of an adherend.

[0012] Means for solving problems

[0013] The inventors of the present invention have discovered that in order to achieve both the re-peelability that allows the aforementioned organic EL information display device to be easily peeled off and the aforementioned followability, the aforementioned problems can be solved by making the foam substrate used in the adhesive tape contain specific constituent components, selecting a specific apparent density range, and selecting a specific tensile modulus, and combining them.

[0014] That is, the present invention relates to an adhesive sheet, which is an adhesive sheet having an adhesive layer directly on one side or both sides of a foam substrate or having an adhesive layer via another layer, wherein the foam substrate contains 30 to 90% by mass of ethylene vinyl acetate copolymer (EVA) and / or ethylene acrylic acid copolymer (EAA), and the apparent density of the foam substrate is 0.20 g / cm 3 ~0.60g / cm 3 And the tensile elastic modulus in the flow direction is 10MPa to 35MPa.

[0015] Effects of the Invention

[0016] The adhesive sheet of the present invention can be peeled off without damaging the organic EL information display device when disassembling the electronic device, and has good followability even for high step difference parts. The adhesive sheet can be used in various scenes represented by, for example, the manufacture of electronic devices such as portable electronic terminals, the fixing of automobile parts, the fixing of interior and exterior decoration of buildings, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a diagram showing a state in which the adhesive sheet of the present invention is attached to an acrylic plate.

[0018] Figure 2 Yes Figure 1 Figure 2 shows an acrylic plate with an adhesive sheet attached to a SUS plate.

[0019] Figure 3 This is a diagram showing a method for measuring the press-fit adhesive strength of the pressure-sensitive adhesive sheet of the present invention using a tensile tester.

[0020] Figure 4 This is a diagram showing a state in which the adhesive sheet of the present invention is attached to an acrylic plate.

[0021] Figure 5 This is a diagram showing a single-sided adhesive tape having a polyethylene terephthalate base material attached to an acrylic plate.

[0022] Figure 6 Yes Figure 5 Place in Figure 4 And pressurized diagram.

[0023] Figure 7 This is a diagram showing a state in which the adhesive sheet of the present invention is attached to an acrylic plate.

[0024] Figure 8 This is a diagram showing a method for evaluating the re-peelability of the adhesive sheet of the present invention.

[0025] Fig. 9 This is a diagram showing a method for evaluating the re-peelability of the adhesive sheet of the present invention. DETAILED DESCRIPTION

[0026] The adhesive sheet of the present invention is an adhesive sheet having an adhesive layer directly or via other layers on one or both sides of a foam substrate, wherein the foam substrate contains 30 to 90% by mass of ethylene vinyl acetate copolymer (EVA) and / or ethylene acrylic acid copolymer (EAA), and the apparent density of the foam substrate is 0.20 g / cm 3 ~0.60g / cm 3 And the tensile elastic modulus in the flow direction is 10MPa to 35MPa.

[0027] (Foam substrate)

[0028] The adhesive sheet of the present invention uses a foam substrate containing 30 to 90% by mass of ethylene vinyl acetate copolymer (EVA) and / or ethylene acrylic acid copolymer (EAA) as a substrate constituting the substrate (core).

[0029] The content of the ethylene vinyl acetate copolymer and / or the ethylene acrylic acid copolymer is more preferably 40 to 80% by mass, and most preferably 50 to 70% by mass. By setting the content of the ethylene vinyl acetate copolymer and / or the ethylene acrylic acid copolymer to this range, it is easy to ensure the strength of the foam that does not tear when peeled off again, and it is easy to ensure the flexibility required for the followability of the step portion.

[0030] The vinyl acetate content (copolymerization ratio) in the ethylene-vinyl acetate copolymer is 20% by mass or less, more preferably 5% by mass or more and 15% by mass or less. By setting the vinyl acetate content in the ethylene-vinyl acetate copolymer to this range, it is easy to ensure the strength of the foam that does not tear when peeled off again, and it is easy to ensure the flexibility required for the followability of the step portion.

[0031] The foam substrate has an apparent density of 0.20 g / cm 3 ~0.60g / cm 3 range of substrates.

[0032] The apparent density of the foam substrate is preferably 0.25 g / cm 3 ~0.55g / cm 3 The range is more preferably 0.30 g / cm 3 ~0.50g / cm 3 By setting the apparent density of the foam substrate to this range, the strength of the foam substrate that does not tear when peeled off can be ensured, and the softness necessary for the followability of the step portion can be ensured. In addition, the aforementioned apparent density refers to the apparent density measured in accordance with JIS K6767, which refers to the apparent density prepared for about 15 cm 3 The amount was obtained by cutting the foam into a 4 cm×5 cm rectangular piece and measuring the mass thereof, and the value was calculated based on the above mass and the above volume.

[0033] The thickness of the foam substrate is preferably in the range of 50 μm to 300 μm, more preferably in the range of 70 μm to 300 μm, and most preferably in the range of 100 μm to 250 μm. If the thickness of the foam substrate is too small, it is difficult to ensure the strength of the foam to the extent that it will not tear when peeled off again. On the other hand, if the thickness of the foam is too large, the thickness of the electronic device itself will increase, which is not ideal from the viewpoint of the design and handling of the electronic device.

[0034] The foam body has a tensile elastic modulus of 10 MPa to 35 MPa in the flow direction. The tensile elastic modulus in the flow direction is preferably 12 MPa to 33 MPa, and most preferably 14 MPa to 29 MPa. By setting the tensile elastic modulus to this range, the strength of the foam body that does not tear when peeled off can be ensured, and the softness necessary for the followability of the step portion can be ensured.

[0035] In addition, the tensile modulus of elasticity in the flow direction of the foam is a value measured in accordance with JIS K7161. Specifically, a foam having a distance (L) between clamps of 20 mm and a width (W) of a test piece of 10 mm is measured using a Tensilon tensile tester at a tensile speed of 10 mm / min under an environment of 23°C and 50% RH, and the tensile modulus of elasticity is calculated by the following method. This evaluation method is suitable as an evaluation of an indicator of whether the foam can be peeled off without tearing when the tape is peeled off again.

[0036] (1) E = (σ2 - σ1) / ε2 - ε1

[0037] E: tensile elastic modulus [Mpa],

[0038] σ1: Stress at strain 0.0005 [MPa]

[0039] σ2: Stress at strain 0.0025 [MPa]

[0040] ε1: strain 0.0005

[0041] ε2: strain 0.0025

[0042] (2)σ1=F1 / (t×W)

[0043] F1: Tensile load at strain 0.0005 [N]

[0044] t: Thickness of the test piece [mm]

[0045] W: Width of test piece [mm]

[0046] (3)σ2=F2 / (t×W)

[0047] F2: Tensile load at strain 0.0025 [N]

[0048] t: Thickness of the test piece [mm]

[0049] W: Width of test piece [mm]

[0050] In addition, as the tensile load at each strain, the tensile load when the distance between the clips increases calculated according to the following formula was used.

[0051] (4)ε=Lt / L

[0052] Lt: Increase in distance between fixtures [mm]

[0053] L: Initial distance between fixtures [mm]

[0054] The aforementioned foam may further contain at least one selected from the group consisting of polyolefin, polyurethane and acrylic polymer. As polyolefin, polyethylene, polypropylene, ethylene-propylene copolymer are preferred, and as acrylic polymer, acrylic rubber and other elastomers are preferred. Among them, in order to improve the tensile strength when peeled off again, it is preferred to contain one or more selected from linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE). Their content is preferably set to 5 to 60% by mass, more preferably set to 10 to 50% by mass, and most preferably set to 20 to 40% by mass. By setting the content to this range, it is easy to take into account the flexibility necessary for following the step difference. In addition, it is preferred to contain an elastomer for improving the following property. As an elastomer, ethylene-propylene rubber (EPDM) is preferred. The content of the elastomer is preferably set to 5 to 40% by mass, and more preferably set to 10 to 30% by mass.

[0055] As the foam, for example, a foam having a cross-linked structure can be used.

[0056] The method for producing the foam is not particularly limited, and for example, the method includes: a step of supplying a foamable resin composition to an extruder for melt kneading, and extruding the foamable resin composition from the extruder into a sheet to produce a foamable resin sheet, wherein the foamable resin composition contains, in addition to ethylene vinyl acetate copolymer (EVA) and / or ethylene acrylic acid copolymer (EAA), a polyolefin resin represented by a polyethylene resin, a thermally decomposable foaming agent, a foaming aid and a colorant as required; a step of crosslinking the foamable resin sheet as required; and a step of foaming the foamable resin sheet.

[0057] The foam obtained by the above method can be melted or softened as needed, and stretched in either or both of its flow direction and width direction. The above stretching can be performed multiple times as needed.

[0058] As a method for producing the foamable resin sheet, for example, the foamable resin sheet can be produced by applying or casting the foamable resin composition on the surface of a release liner or the like and drying the foamable resin sheet.

[0059] The step of crosslinking the foamable resin sheet obtained by the above method can be performed, for example, by irradiating the foamable resin sheet with ionizing radiation or by preparing a foamable resin composition containing an organic peroxide and heating the foamable resin sheet obtained using the composition.

[0060] As the aforementioned ionizing radiation, electron beams, α-rays, β-rays, γ-rays, etc. can be cited. The radiation dose of the ionizing radiation can be appropriately adjusted so that the gel fraction of the resin foam is in the aforementioned preferred range, preferably in the range of 5 to 200 kGy. In addition, from the perspective of easily obtaining a uniform foaming state, the irradiation of the ionizing radiation is preferably performed on both sides of the foamable resin sheet, and more preferably, the radiation dose irradiated on both sides is the same.

[0061] Examples of the organic peroxide include 1,1-bis(tert-butylperoxide)3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxide)cyclohexane, 2,2-bis(tert-butylperoxide)octane, n-butyl-4,4-bis(tert-butylperoxide)valerate, di-tert-butyl peroxide, tert-butylcumyl peroxide, diisopropylbenzene peroxide, α,α′-bis(tert-butylperoxide-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxide)hexyne-3, benzoyl peroxide, cumyl peroxyneodecanoate, tert-butyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxide)hexane, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxyallyl carbonate, etc., which may be used alone or in combination of two or more.

[0062] The amount of the organic peroxide added is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the resin serving as the matrix.

[0063] The step of foaming the foamable resin sheet can be performed, for example, by a method using hot air heating, a method using infrared heating, a method using a salt bath, a method using an oil bath, etc. Among them, a method using hot air heating and a method using infrared heating are preferred.

[0064] When the foamable resin sheet is foamed, a foamable resin sheet containing a thermally decomposable foaming agent or the like may be used.

[0065] The thermal decomposition type foaming agent can be appropriately determined according to the expansion ratio of the foam, and is preferably used in an amount of 1 to 40 parts by mass, more preferably 1 to 30 parts by mass, based on 100 parts by mass of the resin serving as the matrix.

[0066] The stretching step may be performed on the foam obtained by the above method, or may be performed in parallel with the step of foaming the foamable resin sheet.

[0067] The stretching step may be performed continuously while maintaining the molten state in the foaming step, or may be performed by cooling the foamed body after the foaming step and then heating it again.

[0068] Here, the molten state of the foam refers to a state heated to a temperature above the melting point of the matrix resin constituting the foam. In addition, the softened state of the foam refers to a state heated to a temperature above the softening point and below the melting point of the matrix resin constituting the foam.

[0069] As the foam of the present invention, a colored foam can be used for the purpose of imparting design, light-shielding property, concealment, light reflectivity, and light resistance. As a colorant that can be used for the aforementioned coloring, for example, a black colorant can be used, specifically, carbon black, graphite, copper oxide, manganese dioxide, aniline black, perylene black, titanium black, cyanine black, activated carbon, ferrite, magnetite, chromium oxide, iron oxide, molybdenum disulfide, chromium complex, composite oxide-based black pigment, anthraquinone-based organic black pigment, etc. can be used. Among them, as a colorant, carbon black is preferably used in terms of maintenance cost, availability, insulation, and heat resistance.

[0070] As the colorant, a white colorant can be used, specifically, titanium oxide, zinc oxide, aluminum oxide, silicon oxide, magnesium oxide, zirconium oxide, calcium oxide, tin oxide, barium oxide, cesium oxide, yttrium oxide, magnesium carbonate, calcium carbonate, barium carbonate, zinc carbonate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, zinc hydroxide, aluminum silicate, calcium silicate, barium sulfate, calcium sulfate, barium stearate, zinc white, talc, silicon dioxide, aluminum oxide, clay, kaolin, titanium phosphate, mica, gypsum, white carbon, diatomaceous earth, bentonite, lithopone, zeolite, sericite and other inorganic white colorants, silicone resin particles, acrylic resin particles, urethane resin particles, melamine resin particles and other organic white colorants can be used. Among them, as the colorant, aluminum oxide and zinc oxide are preferably used in terms of maintenance cost, availability, color tone and heat resistance.

[0071] In addition, as the foam of the present invention, a foam that contains plasticizers, antioxidants, foaming aids such as zinc oxide, cell nucleus adjusting materials, heat stabilizers, flame retardants such as aluminum hydroxide or magnesium hydroxide, antistatic agents, glass or plastic hollow spheres and beads, metal powders, metal compounds and other fillers, conductive fillers, thermal conductive fillers and other additives as needed within a range that does not impair its physical properties can be used.

[0072] In order to maintain appropriate followability and cushioning properties in the foam, the additive is preferably contained in an amount of 0.1% by mass to 10% by mass, and more preferably 1% by mass to 7% by mass, based on the resin forming the matrix.

[0073] When producing a foam containing additives such as the aforementioned colorant, pyrolyzable foaming agent, and foaming aid, it is preferred to use a masterbatch prepared by pre-kneading a thermoplastic resin having high compatibility with the foamable resin composition and the aforementioned additives in order to prevent color unevenness, partial over-foaming, insufficient foaming, and the like.

[0074] As the foam, in order to improve the adhesion with the adhesive layer and other layers, it is preferred to use a foam having a surface with a wetting index of 36 mN / m or more based on a wetting agent, more preferably a foam having a surface with a wetting index of 40 mN / m or more, and further preferably a foam having a surface with a wetting index of 48 mN / m or more. As a method for adjusting the wetting index of the surface of the foam to the above range, surface treatment methods such as corona treatment, flame treatment, plasma treatment, hot air treatment, ozone treatment, ultraviolet treatment, and coating of an easy-adhesion treatment agent can be cited.

[0075] (adhesive layer)

[0076] As the adhesive sheet, one having an adhesive layer directly or via another layer on one side or both sides of the foam can be used.

[0077] As the adhesive that can be used in the formation of the aforementioned adhesive layer, for example, an acrylic adhesive, a urethane adhesive, a synthetic rubber adhesive, a natural rubber adhesive, a silicone adhesive, etc. can be used. Preferably, an acrylic adhesive containing an acrylic polymer obtained by polymerizing a monomer component containing a (meth)acrylic acid monomer and containing a tackifying resin, a cross-linking agent, etc. as needed is used.

[0078] As the (meth)acrylic acid monomer that can be used in the production of the acrylic polymer, for example, (meth)acrylic acid esters having an alkyl group having 1 to 12 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, can be used.

[0079] Among them, as the (meth)acrylic acid monomer, it is preferred to use a (meth)acrylate having an alkyl group with 4 to 12 carbon atoms, and it is further preferred to use a (meth)acrylate having an alkyl group with 4 to 8 carbon atoms. In terms of achieving both excellent adhesion and excellent followability, it is particularly preferred to use either or both of n-butyl acrylate and 2-ethylhexyl acrylate.

[0080] The (meth)acrylate having an alkyl group having 1 to 12 carbon atoms is preferably used in an amount of 60% by mass or more, more preferably in a range of 80% by mass to 98.5% by mass, relative to the total amount of monomers used in the production of the acrylic polymer. In terms of achieving both excellent adhesion and excellent followability, it is further preferably used in a range of 90% by mass to 98.5% by mass.

[0081] In addition, when producing the acrylic polymer, a highly polar vinyl monomer may be used as a monomer. As the highly polar vinyl monomer, one or more vinyl monomers having a hydroxyl group, vinyl monomers having a carboxyl group, vinyl monomers having an amide group, etc. may be used in combination.

[0082] As the monomer having a hydroxyl group, for example, (meth)acrylates having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate can be used.

[0083] As the vinyl monomer having a carboxyl group, for example, acrylic acid, methacrylic acid, itaconic acid, maleic acid, (meth)acrylic acid dimer, crotonic acid, ethylene oxide-modified succinic acid acrylate, etc. can be used. Among them, acrylic acid is preferably used.

[0084] As the monomer having an amide group, for example, N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, acrylamide, N,N-dimethylacrylamide, etc. can be used.

[0085] As the high polar vinyl monomer, in addition to the above-mentioned monomers, vinyl acetate, ethylene oxide-modified succinic acid acrylate, 2-acrylamide-2-methylpropanesulfonic acid, etc. can be used.

[0086] The high polarity vinyl monomer is preferably used in an amount of 1.5 to 20% by mass, more preferably 1.5 to 10% by mass, relative to the total amount of monomers used in the production of the acrylic polymer. In terms of achieving both excellent adhesive strength and excellent followability, it is further preferably used in an amount of 2 to 8% by mass.

[0087] When a material containing a crosslinking agent described below is used as the adhesive, it is preferred to use an acrylic polymer having a functional group reactive with the functional group of the crosslinking agent. Examples of the functional group that the acrylic polymer may have include a hydroxyl group.

[0088] The hydroxyl group can be introduced into the acrylic polymer by, for example, using a vinyl monomer having a hydroxyl group as the monomer.

[0089] The vinyl monomer having a hydroxyl group is used in an amount of preferably 0.01 to 1.0% by mass, more preferably 0.03 to 0.3% by mass, based on the total amount of monomers used for producing the acrylic polymer.

[0090] The acrylic polymer can be produced by polymerizing the monomers by solution polymerization, bulk polymerization, suspension polymerization, emulsion polymerization or the like. In terms of improving the production efficiency of the acrylic polymer, solution polymerization is preferably used.

[0091] Examples of the solution polymerization method include a method in which the monomer, a polymerization initiator, and an organic solvent are mixed and stirred at a temperature preferably in the range of 40° C. to 90° C. to perform radical polymerization.

[0092] As the aforementioned polymerization initiator, for example, peroxides such as benzoyl peroxide or lauroyl peroxide; azo-based thermal polymerization initiators such as azobisisobutyronitrile; acetophenone-based photopolymerization initiators, benzoin ether-based photopolymerization initiators, benzyl ketal-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzophenone-based photopolymerization initiators, etc. can be used.

[0093] The acrylic polymer obtained by the above method may be in a state of being dissolved or dispersed in an organic solvent, for example, when produced by a solution polymerization method.

[0094] As the acrylic polymer, a polymer having a weight average molecular weight of 400,000 to 3,000,000 is preferably used, and a polymer having a weight average molecular weight of 700,000 to 2,500,000 is more preferably used.

[0095] The weight average molecular weight is a value calculated by gel permeation chromatography (GPC) in terms of standard polystyrene. Specifically, the weight average molecular weight can be measured under the following conditions using a GPC device (HLC-8320GPC) manufactured by Tosoh Corporation.

[0096] Sample concentration: 0.5 mass% (tetrahydrofuran solution)

[0097] Sample injection volume: 100 μL

[0098] Eluent: Tetrahydrofuran

[0099] Flow rate: 1.0mL / min

[0100] Measurement temperature: 40℃

[0101] Main column: TSKgel GMHHR-H (20) 2 pieces

[0102] Guard column: TSKgel HXL-H

[0103] Detector: Differential refractometer

[0104] Weight average molecular weight of standard polystyrene: 10,000 to 20,000,000 (manufactured by Tosoh Corporation)

[0105] As the adhesive that can be used for forming the adhesive layer, an adhesive containing a tackifier resin is preferably used in terms of achieving both excellent adhesive strength to an adherend or a foam and excellent followability.

[0106] As the aforementioned tackifying resin, for example, rosin-based tackifying resin, polymerized rosin-based tackifying resin, polymerized rosin ester-based tackifying resin, rosin phenol-based tackifying resin, stabilized rosin ester-based tackifying resin, disproportionated rosin ester-based tackifying resin, hydrogenated rosin ester-based tackifying resin, terpene-based tackifying resin, terpene phenol-based tackifying resin, petroleum resin-based tackifying resin, (meth)acrylate resin-based tackifying resin, etc. can be used. When a latex-type adhesive is used as the aforementioned adhesive, it is preferable to also use a latex-type tackifying resin as the aforementioned tackifying resin.

[0107] As the aforementioned tackifier resin, it is preferred to use one or a combination of two or more of the aforementioned disproportionated rosin ester tackifier resins, polymerized rosin ester tackifier resins, rosin phenol tackifier resins, hydrogenated rosin ester tackifier resins, (meth)acrylate resins, terpene phenol resins, and petroleum resins.

[0108] As the aforementioned tackifier resin, it is preferred to use a tackifier resin having a softening point in the range of 30°C to 180°C, and it is more preferred to use a tackifier resin in the range of 70°C to 140°C in order to achieve both excellent adhesion to the adherend and the foam substrate (B) and excellent followability. When the aforementioned (meth)acrylate tackifier resin is used, it is preferred to use a tackifier resin having a glass transition temperature of 30°C to 200°C, and it is more preferred to use a tackifier resin having a glass transition temperature of 50°C to 160°C.

[0109] The tackifier resin is preferably used in an amount of 5 to 65 parts by mass based on 100 parts by mass of the acrylic polymer, and more preferably used in an amount of 8 to 55 parts by mass in order to achieve both excellent adhesion to an adherend or a foam and excellent followability.

[0110] As the adhesive used for forming the adhesive layer, a crosslinking agent is preferably used in order to ensure excellent adhesive strength to an adherend or a foam.

[0111] As the crosslinking agent, for example, an isocyanate crosslinking agent, an epoxy crosslinking agent, a metal chelate crosslinking agent, an aziridine crosslinking agent, etc. can be used. Among them, as the crosslinking agent, it is preferred to use either or both of an isocyanate crosslinking agent and an epoxy crosslinking agent that are highly reactive with the acrylic polymer, and it is more preferred to use an isocyanate crosslinking agent.

[0112] As the isocyanate crosslinking agent, for example, toluene diisocyanate, naphthalene-1,5-diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, xylene diisocyanate, trimethylolpropane-modified toluene diisocyanate, etc. can be used, and toluene diisocyanate and trimethylolpropane-modified toluene diisocyanate are preferably used.

[0113] The cross-linking agent is preferably selected and used in an amount so that the gel fraction of the adhesive layer relative to toluene becomes 40 to 80%, and more preferably selected and used in an amount so that the gel fraction becomes 30 mass % to 70 mass %. In order to obtain an adhesive sheet that takes into account both excellent adhesion to the adherend and excellent followability to the foam substrate, it is further preferably selected and used in an amount so that the gel fraction becomes 35 mass % to 65 mass %.

[0114] In addition, the said gel fraction is the value measured by the method shown below.

[0115] The adhesive was applied onto the release-treated surface of the release liner to a thickness of 50 μm after drying, and then dried at 100° C. for 3 minutes and aged at 40° C. for 2 days to form an adhesive layer.

[0116] The adhesive layer was cut into a square of 50 mm in length and 50 mm in width to prepare a test piece.

[0117] After measuring the mass (G1) of the test piece, the test piece was immersed in toluene in an environment of 23°C for 24 hours.

[0118] After the immersion, the mixture of the test piece and toluene was filtered using a 300-mesh metal sieve to extract the toluene-insoluble component. The insoluble component was dried under an environment of 110° C. for 1 hour, and then the mass (G2) was measured.

[0119] Based on the mass (G1), the mass (G2) and the following formula, the gel fraction was calculated.

[0120] Gel fraction (mass %) = (G2 / G1) × 100

[0121] As the aforementioned adhesive, for example, an adhesive containing additives such as plasticizers, softeners, antioxidants, flame retardants, glass or plastic fibers / spheres, beads, metals, metal oxides, metal nitrides and other fillers, pigments, dyes and other colorants, leveling agents, thickeners, water repellents, defoaming agents and the like can be used.

[0122] The pressure-sensitive adhesive layer formed using the pressure-sensitive adhesive preferably has a loss tangent (tan δ) peak at a frequency of 1 Hz of -40°C to 15°C. When the pressure-sensitive adhesive layer has a loss tangent peak within this range, good adhesion to an adherend at room temperature can be easily imparted.

[0123] The loss tangent (tanδ) at a frequency of 1 Hz is calculated from the storage modulus (G') and loss modulus (G") obtained by the dynamic viscoelasticity measurement based on temperature dispersion, using the formula tanδ = G" / G'. In the measurement of dynamic viscoelasticity, a viscoelasticity tester (manufactured by TA Instruments Japan, trade name: ARES G2) is used. For an adhesive layer formed to a thickness of about 2 mm, a test piece is sandwiched between parallel disks of 8 mm in diameter serving as a measuring part of the same tester, and the storage modulus (G') and loss modulus (G") from -50°C to 150°C are measured at a frequency of 1 Hz.

[0124] In order to achieve both excellent adhesion to the adherend and the foam and excellent followability, the thickness of the pressure-sensitive adhesive layer used in the present invention is preferably 5 μm to 100 μm, more preferably 15 μm to 80 μm, and particularly preferably 25 μm to 75 μm.

[0125] (Adhesive sheet)

[0126] The adhesive sheet of the present invention preferably has a strength value of 40 N / cm when the press-in adhesive strength is measured in a frame shape with a width of 1 mm. 2 More than 50 N / cm 2 Above, most preferably 60N / cm 2 By increasing the bonding strength in this method, it is possible to ensure the bonding strength necessary for fixing the components and ensuring waterproofness.

[0127] The adhesive sheet of the present invention can be manufactured, for example, by the following methods: a direct method in which the adhesive is directly applied to the foam and dried; or a transfer method in which the adhesive is applied to a release sheet and dried to form an adhesive layer, and then the adhesive layer is attached to the foam. When an adhesive containing an acrylic polymer and a crosslinking agent is used as the adhesive to form the adhesive layer, in terms of excellent adhesion to the adherend and the foam substrate and excellent tracking properties, it is preferred to laminate the adhesive layer on one or both sides of the foam by the direct method or the transfer method, and then age it for about 2 to 7 days, preferably at 20°C to 50°C, more preferably at 23°C to 45°C.

[0128] As the adhesive sheet of the present invention, a thickness of 400 μm or less is preferred because it is easy to contribute to the thinning of electronic devices, more preferably 100 μm to 300 μm, further preferably 150 μm to 300 μm, and most preferably 200 μm to 300 μm. Since the adhesive sheet uses a foam having the aforementioned specific apparent density and tensile elastic modulus, the total thickness of the adhesive sheet is as described above, and even when peeled off during re-peeling, the foam is not easy to tear, and can take into account good tracking properties of the step portion.

[0129] As the adhesive sheet, a sheet further including other layers as necessary in addition to the foam and the adhesive layer may be used.

[0130] Examples of the other layers include laminate layers such as polyester films, light shielding layers, light reflecting layers, and heat conductive layers such as metal layers in order to impart dimensional stability, good tensile strength, and removability to the pressure-sensitive adhesive sheet.

[0131] The adhesive sheet of the present invention may have a release sheet laminated on the surface of the adhesive layer.

[0132] As the aforementioned release sheet, for example, a release sheet obtained by subjecting at least one surface of a film, paper, nonwoven fabric, cloth, foam sheet, metal substrate, and a laminate thereof obtained using a synthetic resin such as polyethylene, polypropylene, or polyester to a release treatment such as silicone treatment, long-chain alkyl treatment, or fluorine treatment can be used.

[0133] The pressure-sensitive adhesive sheet of the present invention is particularly suitable for use in applications where, for example, it is required to be bonded and fixed to a site having projections and depressions or a large step, and it is required to fix the adhered member without damaging it when it is peeled off.

[0134] The aforementioned members having projections and depressions or large step differences are often used as members in industrial applications such as electronic terminals such as car navigation systems and smartphones, and automobiles, building materials, OA, and home appliance industries.

[0135] Specific examples of the member include two or more types of housings and lens members constituting the electronic terminal.

[0136] Articles such as electronic terminals obtained by fixing two or more housings and lens members using the adhesive sheet of the present invention have excellent adhesive strength, can be peeled off again when disassembling, and have excellent waterproof properties.

[0137] Example

[0138] Hereinafter, the present invention will be described in more detail by way of Examples and Comparative Examples.

[0139] [Preparation Example 1] Method for producing acrylic polymer (A-1)

[0140] In a reaction container equipped with a stirrer, a reflux cooling tube, a nitrogen inlet tube, and a thermometer, 95.9 parts by mass of n-butyl acrylate, 4 parts by mass of acrylic acid, 0.1 parts by mass of 2-hydroxyethyl acrylate, and 200 parts by mass of ethyl acetate were added, and the temperature was raised to 72° C. while stirring and blowing nitrogen.

[0141] Next, 2 parts by mass (solid content: 0.1 mass%) of a 2,2′-azobis(2-methylbutyronitrile) solution previously dissolved in ethyl acetate was added to the mixture, and the mixture was kept at 72° C. for 4 hours and then kept at 75° C. for 5 hours under stirring.

[0142] Next, the mixture was filtered through a 200-mesh metal screen to obtain an acrylic polymer (A-1) solution having a weight average molecular weight of 1.86 million (nonvolatile content: 33% by mass).

[0143] [Preparation Example 2] Method for producing acrylic polymer (A-2)

[0144] In a reaction container equipped with a stirrer, a reflux cooling tube, a nitrogen inlet tube, and a thermometer, 63.9 parts by mass of n-butyl acrylate, 32 parts by mass of 2-ethylhexyl acrylate, 4 parts by mass of acrylic acid, 0.1 parts by mass of 4-hydroxybutyl acrylate, and 200 parts by mass of ethyl acetate were added, and the temperature was raised to 72° C. while blowing nitrogen gas under stirring.

[0145] Next, 2 parts by mass (solid content: 0.1 mass%) of a 2,2′-azobis(2-methylbutyronitrile) solution previously dissolved in ethyl acetate was added to the mixture, and the mixture was kept at 72° C. for 4 hours and then kept at 75° C. for 5 hours under stirring.

[0146] Next, the mixture was filtered through a 200-mesh metal screen to obtain an acrylic polymer (A-2) solution having a weight average molecular weight of 750,000 (nonvolatile content: 33% by mass).

[0147] [Adhesive composition (A)]

[0148] In a container, 100 parts by mass of the acrylic polymer (A-1), 10 parts by mass of a polymerized rosin ester tackifier resin D-125 (manufactured by Arakawa Chemical Industries, Ltd.) and 15 parts by mass of a disproportionated rosin ester tackifier resin A-100 (manufactured by Arakawa Chemical Industries, Ltd.) were mixed and stirred, and then ethyl acetate was added to obtain an adhesive composition (A) having a solid content of 31% by mass.

[0149] [Adhesive composition (B)]

[0150] In a container, 100 parts by mass of the acrylic polymer (A-2), 10 parts by mass of a polymerized rosin ester tackifier resin D-125 (manufactured by Arakawa Chemical Industries, Ltd.) and 15 parts by mass of a disproportionated rosin ester tackifier resin A-100 (manufactured by Arakawa Chemical Industries, Ltd.) were mixed and stirred, and then ethyl acetate was added to obtain an adhesive composition (B) having a solid content of 31% by mass.

[0151] [Adhesive (A1)]

[0152] To 100 parts by mass of the adhesive composition (A), 1.4 parts by mass of BURNOCK D-40 (manufactured by DIC Corporation, trimethylolpropane adduct of toluene diisocyanate, isocyanate content of 7% by mass, non-volatile component of 40% by mass) was added as a crosslinking agent, and the mixture was stirred and mixed until uniform, and then filtered through a 100-mesh metal mesh to obtain an adhesive (A1) having a gel fraction of 50%.

[0153] [Adhesive (A2)]

[0154] 0.7 parts by mass of BURNOCK D-40 as a crosslinking agent was added to 100 parts by mass of the adhesive composition (A), and the mixture was stirred and mixed until uniform, and then filtered through a 100-mesh metal sieve to obtain an adhesive (A2) having a gel fraction of 30%.

[0155] [Adhesive (A3)]

[0156] 2.1 parts by mass of BURNOCK D-40 as a crosslinking agent was added to 100 parts by mass of the adhesive composition (A), and the mixture was stirred and mixed until uniform, and then filtered through a 100-mesh metal sieve to obtain an adhesive (A3) having a gel fraction of 70%.

[0157] [Adhesive (B)]

[0158] Next, 1.4 parts by mass of BURNOCK D-40 as a crosslinking agent was added to 100 parts by mass of the adhesive composition (B), and the mixture was stirred and mixed until uniform, and then filtered through a 100-mesh metal sieve to obtain an adhesive (B) having a gel fraction of 50%.

[0159] [Example 1]

[0160] The adhesive (A1) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 50 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0161] Next, the adhesive layer was attached to both surfaces of the foam 1 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured for 48 hours at 40° C. to prepare an adhesive sheet.

[0162] [Example 2]

[0163] An adhesive sheet was obtained by the same method as in Example 1 except that the foam 2 described in Table 1 was used instead of the foam 1.

[0164] [Example 3]

[0165] An adhesive sheet was obtained by the same method as in Example 1 except that the foam 3 described in Table 1 was used instead of the foam 1.

[0166] [Example 4]

[0167] An adhesive sheet was obtained by the same method as in Example 1 except that the foam 4 described in Table 1 was used instead of the foam 1.

[0168] [Example 5]

[0169] An adhesive sheet was obtained by the same method as in Example 1 except that the foam 5 described in Table 1 was used instead of the foam 1.

[0170] [Example 6]

[0171] An adhesive sheet was obtained by the same method as in Example 1 except that the foam 6 described in Table 1 was used instead of the foam 1.

[0172] [Example 7]

[0173] An adhesive sheet was obtained by the same method as in Example 1 except that foam 7 described in Table 1 was used instead of foam 1.

[0174] [Example 8]

[0175] An adhesive sheet was obtained by the same method as in Example 1 except that the foam 8 described in Table 1 was used instead of the foam 1.

[0176] [Example 9]

[0177] An adhesive sheet was obtained by the same method as in Example 1 except that foam 9 described in Table 1 was used instead of foam 1.

[0178] [Example 10]

[0179] The adhesive (A1) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 15 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0180] Next, the adhesive layer was attached to both surfaces of the foam 10 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured in an environment of 40° C. for 48 hours to prepare an adhesive sheet.

[0181] [Example 11]

[0182] The adhesive (A1) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 15 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0183] Next, the adhesive layer was attached to both surfaces of the foam 11 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured in an environment of 40° C. for 48 hours to prepare an adhesive sheet.

[0184] [Example 12]

[0185] The adhesive (A1) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 25 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0186] Next, the adhesive layer was attached to both surfaces of the foam 12 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured in an environment of 40° C. for 48 hours to prepare an adhesive sheet.

[0187] [Example 13]

[0188] The adhesive (A1) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 50 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0189] Next, the adhesive layer was attached to both surfaces of the foam 13 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured in an environment of 40° C. for 48 hours to prepare an adhesive sheet.

[0190] [Example 14]

[0191] The adhesive (A1) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 50 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0192] Next, the adhesive layer was attached to both surfaces of the foam 14 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured in an environment of 40° C. for 48 hours to prepare an adhesive sheet.

[0193] [Example 15]

[0194] The adhesive (A2) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 50 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0195] Next, the adhesive layer was attached to both surfaces of the foam 5 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured in an environment of 40° C. for 48 hours to prepare an adhesive sheet.

[0196] [Example 16]

[0197] The adhesive (A3) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 50 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0198] Next, the adhesive layer was attached to both surfaces of the foam 5 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured in an environment of 40° C. for 48 hours to prepare an adhesive sheet.

[0199] [Example 17]

[0200] The adhesive (B) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 50 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0201] Next, the adhesive layer was attached to both surfaces of the foam 5 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured in an environment of 40° C. for 48 hours to prepare an adhesive sheet.

[0202] [Comparative Example 1]

[0203] The adhesive (A1) was applied onto the surface of the release liner using a bar coater so that the thickness of the adhesive layer after drying would be 50 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer.

[0204] Next, the adhesive layer was attached to both surfaces of the foam 15 shown in Table 1 whose surface was corona treated to adjust the wettability index to 50 mN / m, and cured in an environment of 40° C. for 48 hours to prepare an adhesive sheet.

[0205] [Comparative Example 2]

[0206] An adhesive sheet was obtained by the same method as in Comparative Example 1 except that the foam 16 described in Table 1 was used instead of the foam 15 .

[0207] [Comparative Example 3]

[0208] An adhesive sheet was obtained by the same method as in Comparative Example 1 except that the foam 17 described in Table 1 was used instead of the foam 15 .

[0209] [Comparative Example 4]

[0210] An adhesive sheet was obtained by the same method as in Comparative Example 1 except that the foam 18 described in Table 1 was used instead of the foam 15 .

[0211] [Table 1]

[0212]

[0213] [Table 2]

[0214]

[0215] [Table 3]

[0216]

[0217] [Table 4]

[0218]

[0219] The apparent density and tensile modulus of the foam in Table 1 were measured by the same method as described in the specification of the present application.

[0220] [Evaluation method of press-fit bond strength]

[0221] 1) At 23°C, the adhesive sheet obtained above was punched into a window frame shape of 15 mm square and 1 mm wide, and then attached to an acrylic plate (Mitsubishi Rayon Co., Ltd. ACRYLITE MR200 "trade name", color: transparent, the same below) of 2 mm thickness and 20 mm square ( Figure 1 ).

[0222] 2) Next, the acrylic plate with adhesive sheet prepared in 1) was attached to a 2 mm thick, 30×60 mm rectangular SUS plate having a hole with a diameter of 10 mm in the center, so that the center of the acrylic plate and the center of the SUS plate were aligned, and reciprocated pressure was applied once with a 2 kg roller, and then allowed to stand at 23° C. for 1 hour to prepare a test piece ( Figure 2 ).

[0223] 3) Using a tensile testing machine equipped with a stainless steel probe of 8 mm in diameter, the acrylic plate was pressed at 10 mm / min from the SUS side of the test piece through the hole of the SUS plate to measure the peel strength of the acrylic plate ( Figure 3 ).

[0224] [Evaluation method of step tracking performance]

[0225] 1) Using the adhesive sheet obtained above, a frame-shaped sample with an outer shape of 64 mm × 43 mm and a width of 1 mm was prepared and attached to an acrylic plate with a thickness of 2 mm and an outer shape of 65 mm × 45 mm ( Figure 4 ).

[0226] 2) Next, two sheets of single-sided adhesive tape (for forming step difference) of polyethylene terephthalate (PET) substrate with different thicknesses (30 μm, 40 μm, 50 μm, 60 μm), widths of 5 mm, and lengths of 45 mm were attached in parallel to the central portion of another acrylic plate with a thickness of 2 mm and an outer shape of 65 mm × 45 mm at a longitudinal interval of 1 cm to prepare an acrylic plate with step difference ( Figure 5 ).

[0227] 3) At 23°C, after placing an acrylic plate with an adhesive sheet on the adhesive tape portion of the acrylic plate with a step, reciprocate pressure with a 2 kg roller from the end once ( Figure 6 ).

[0228] 4) The following state of the adhesive sheet near the step was visually evaluated from the acrylic plate side having the step.

[0229] A: There are no voids such as bubbles at the interface between the step portion and the adhesive sheet up to a step of 60 μm.

[0230] B: No voids such as bubbles existed at the interface between the step portion and the adhesive sheet up to a step difference of 50 μm, but voids such as bubbles existed at the interface between the step portion and the adhesive sheet when the step difference was 60 μm.

[0231] C: No voids such as bubbles exist at the interface between the step portion and the adhesive sheet up to a step height of 40 μm, but voids such as bubbles exist at the interface between the step portion and the adhesive sheet when the step height is 50 μm or more.

[0232] D: There are no voids such as bubbles at the interface between the step portion and the adhesive sheet up to a step height of 30 μm, but there are voids such as bubbles at the interface between the step portion and the adhesive sheet when the step height is 40 μm or more.

[0233] E: When the step is 30 μm, voids such as bubbles exist at the interface between the step and the adhesive sheet.

[0234] [Re-peeling adaptability]

[0235] 1) Prepare two samples of adhesive sheets with a length of 40 mm and a width of 2 mm, and attach them in parallel to an acrylic plate with a thickness of 2 mm and a size of 50 mm × 50 mm ( Figure 7 ).

[0236] Next, a PET film plate with a thickness of 0.05 mm and an outer size of 50 mm×50 mm was attached, and each sample was reciprocally pressed once with a 2 kg roller, and then left at 23° C. for 24 hours to prepare a test piece.

[0237] 2) For the test piece, the tape state when the PET film is peeled off in the vertical direction at 23°C is evaluated ( Figure 8 ).

[0238] 3) Next, the ease of peeling when the adhesive sheet remaining on the PET film or acrylic plate was peeled off by hand in a direction with a peeling angle of about 135 degrees was evaluated ( Fig. 9 ).

[0239] A: When the PET film was peeled in the vertical direction, peeling did not occur due to cracking of the foam substrate layers. Furthermore, even when the adhesive sheet remaining on the PET film or acrylic plate was peeled, peeling did not occur due to cracking of the substrate layers.

[0240] B: When the PET film was peeled in the vertical direction, peeling occurred without rupture of the foam substrate layers. When the adhesive sheet remaining on the PET film or acrylic plate was peeled, rupture of the foam substrate layers occurred, but the tape could be peeled off by re-stretching.

[0241] C: When the PET film was peeled off in the vertical direction, the foam substrate was peeled off without any interlayer rupture. When the adhesive sheet remaining on the PET film or acrylic plate was peeled off, the foam substrate was ruptured between the layers, and even if it was stretched again by hand, the interlayer rupture occurred and it could not be peeled off.

[0242] D: When the PET film was peeled off in the vertical direction, the foam substrate interlayer cracked. In addition, when the adhesive sheet remaining on the PET film or acrylic plate was peeled off, the substrate interlayer cracked, and even if it was stretched again by hand, the interlayer cracked and could not be peeled off.

[0243] [Table 5]

[0244]

[0245] [Table 6]

[0246]

[0247] [Table 7]

[0248]

[0249] [Table 8]

[0250]

[0251] The above results show that Examples 1 to 17 of the present invention successfully achieved both step followability and removability while maintaining appropriate adhesive strength. On the other hand, Comparative Examples 1 and 3 showed poor step followability, and Comparative Examples 2 to 4 showed poor removability.

[0252] Explanation of symbols

[0253] 1 Acrylic sheet

[0254] 2 Adhesive sheet

[0255] 3 SUS board

[0256] 4 Stainless steel probe

[0257] 21 Adhesive sheet

[0258] 22 Acrylic Sheet

[0259] 23 Acrylic sheet

[0260] 24 Polyethylene terephthalate-based single-sided adhesive tape

[0261] 25 Evaluation of step tracking performance

[0262] 31 Acrylic sheet

[0263] 32 Adhesive sheet

[0264] 33 PET film.

Claims

1. An adhesive sheet having an adhesive layer directly on one side or both sides of a foam substrate or having an adhesive layer via another layer, wherein the foam substrate contains 30 to 90% by mass of ethylene vinyl acetate copolymer and / or ethylene acrylic acid copolymer, and the apparent density of the foam substrate is 0.20 g / cm 3 ~0.60g / cm 3 The tensile modulus in the flow direction measured according to JIS K7161 is 10 MPa to 35 MPa, the foam substrate further contains an elastomer, the foam substrate has a thickness of 100 to 300 μm, and the sheet has a thickness of 150 to 400 μm. 2 . The adhesive sheet according to claim 1 , wherein the adhesive layer has a gel fraction of 40 to 80%. 3 . The adhesive sheet according to claim 1 , wherein the foam substrate further contains at least one selected from the group consisting of polyolefins, polyurethanes, and acrylic polymers. 4 . The adhesive sheet according to claim 3 , wherein the content of at least one selected from the group consisting of polyolefins, polyurethanes, and acrylic polymers is 5 to 60% by mass. 5 . The adhesive sheet according to claim 3 , wherein the polyolefin is at least one selected from the group consisting of linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, and high-density polyethylene.

6. The adhesive sheet according to claim 1 or 2, wherein the strength value of the press-in adhesive strength measured in a frame shape with a width of 1 mm is 40 N / cm 2 above. 7 . An electronic device having a structure in which two or more adherends are bonded together by the adhesive sheet according to claim 1 .

Citation Information

Patent Citations

  • Expanded sheet and adhesive tape

    JP2008274073A

  • Double sided adhesive tape

    CN101857780A

  • Polyolefin resin foam sheet and adhesive tape

    CN106715550A

  • Pressure-sensitive adhesive tape

    CN104039912A

  • Pressure sensitive adhesive tape

    CN104053734A